The Australian Curriculum: Excellence or Equity. A Rural Perspective - Drummond, Aaron (Australian and International Journal of Rural Education, 2012)
“The Australian Curriculum promotes excellence and equity in education.” (ACARA, 2012a, p. 1) In 2008 it was agreed by the Australian Education Ministers that a national curriculum be implemented with the rationale that it would help to ensure high quality education for all young Australians (ACARA, 2012b). One reason for the shift to a standardised national curriculum is so that “School and curriculum authorities can collaborate to ensure high quality teaching and learning materials are available for all schools.” (ACARA, 2012b, p. 1, emphasis added). The Australian curriculum represents a huge shift in the manner in which education is legislated and delivered in Australia. Though there are benefits to the implementation of a national curriculum, there are also a variety of challenges. What does the implementation of the Australian Curriculum mean for nonmetropolitan schools? The statement by ACARA is indicative that rural schools will benefit equally from the implementation of the Australian Curriculum. However, some unique characteristics of rural areas mean that additional support may be required to ensure the successful implementation of a national curriculum in rural areas. Difficulty with accessing resources in rural areas may result in further challenges for rural schools. To support a nationwide implementation process that results in an equitable curriculum for all Australian children irrespective of their location, it may be necessary to differentiate support to rural and metropolitan schools. Drawing upon two surveys, one on the Australian Curriculum in rural areas previously published in Curriculum Perspectives and the other a survey of both rural and metropolitan school leaders on the implementation process, I explore the implementation of the Australian Curriculum in rural contexts. Although rural school leaders are overall supportive of the Australian curriculum, they do express dissatisfaction with the implementation process, specifically with the support they are receiving. The delay in the implementation of the Australian Curriculum appears to have resulted in marginally higher funding for non-metropolitan schools, but the overall funds available are both objectively and subjectively low. In order to ensure that the implementation of the Australian Curriculum is successful and remedying (c.f. enhancing) rural inequities, much more needs to be done to support its implementation in non-metropolitan schools.